The Impact of Company Characteristics Behavior (Size, Profile and Institutional Ownership) On Disclosure of Corporate Social Responsibility (Journal of Entrepreneurship and Business, 2021)
The term Corporate social responsibility (CSR) defined as corporate social responsibility, which is an issue of corporate environmental management and is value-added for many multinational companies, including companies located in Indonesia. Corporate awareness in maintaining the environment around the company is much demanded by community social institutions (NGO-environment), to maintain the natural and social balance of the community. Therefore, the implementation and disclosure of CSR for the company is expected to be able to add value to the sustainability of the company itself. Company awareness in establishing good relations with the community, stakeholders, and government can be done for the existence of the company through CSR disclosure, disclosure of financial performance, and the institutional structure of corporate ownership. The company orientation, which originally only a shareholder orientation with the economic orientation paradigm being a stakeholder orientation, will have social and environmental impacts on the company's operations. This study conducted to determine the effect of corporate characteristics behavior (size, profile, institutional ownership) on disclosure of corporate social responsibility. CSR disclosure uses the Corporate Social Responsibility Index (GRI G4). The sampling method used was purposive sampling with a sample of 150 companies listed on the Indonesia Stock Exchange for 2017-2019. The data used are secondary data obtained from www.idx.co.id and the official websites of all related companies. The data analysis method used is multiple regression analysis (OLS). The results of hypothesis testing conclude that the company profile and institutional ownership structure significantly influence the disclosure of social responsibility; Meanwhile, the size of the company does not significantly affect the disclosure of social responsibility.
Keywords: Array; Array